Using Poloxamer® 407 as Building Block of Amphiphilic Poly(ether urethane)s: Effect of its Molecular Weight Distribution on Thermo-Sensitive Hydrogel Performances in the Perspective of Their Biomedical Application - Laurano, Rossella; Abrami, Michela; Grassi, Mario; Ciardelli, Gianluca; Boffito, Monica; Chiono, Valeria (Frontiers in Materials, 2020)
Due to its hydroxyl terminal groups, Poloxamer® 407 (P407), a commercially available poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) triblock copolymer can be used as macrodiol for the synthesis of high molecular weight amphiphilic poly(ether urethane)s (PEUs). This work was aimed at studying the effect of P407 purification by removing PEO-PPO diblock copolymer by-products on the chemical properties of PEU polymer and the physical properties of PEU hydrogels. Removal of PEO-PPO diblock copolymers (P407_P) was found to preserve the thermo-responsiveness of resulting P407 hydrogels, although slightly lower gelation onset temperature (Tonset) was found for P407_P (15.3 °C) vs. P407 (16.7 °C) hydrogels (25% w/V) as assessed through temperature ramp test. P407 and P407_P were then reacted with 1,6-diisocyanatohexane and 1,4-cyclohexanedimethanol to synthesize two different PEUs, coded as CHP407 and CHP407_P, respectively. Lower Number Average Molecular Weight ((M_n) and higher polydispersity Index (D) was measured for CHP407 ((M_n):34kDa, D:1.6) respect to CHP407_P ((M_n):40kDa, D:1.4) as a consequence of macrodiol purification. CHP407_P hydrogels formed bigger micelles (43.9±4.1 nm vs 28.7±4 nm) while showed similar critical micellar temperatures (22.1 °C vs 21.6 °C) respect to CHP407 formulations. Sol-to-gel transition of CHP407 and CHP407_P hydrogels was similar while CHP407_P gelation time at 37 °C was longer as assessed by tube inverting test. The rheological analysis showed slightly lower Tonset for CHP407_P hydrogels (15%w/V), probably due to bigger micelle size, promoting micellar assembly. However, CHP407_P hydrogels showed a significant lower critical strain than CHP407 hydrogels, as assessed by strain sweep test, suggesting their higher brittleness due to a lower density of intermicellar bridge chains. Nano-scale hydrogel characterization by Low-Field Nuclear Magnetic Resonance spectroscopy supported previous findings, showing lower spin-spin relaxation time (i.e., 1259 ms) for CHP407_P than for CHP407 hydrogels (i.e., 1560 ms) at 37 °C, which suggested the formation of a more tightly packed network for CHP407_P than CHP407 hydrogel. Finally lower swelling capability and resistance against dissolution were measured for CHP407_P hydrogels. Overall, results suggested that the heterogeneous structure in the CHP407 hydrogel network caused by the presence of diblock copolymer-based macrodiols improved PEU hydrogel properties in light of their applicability in the biomedical field.